Ontological Restoration of Insan Kamil: Navigating the Critical Reasoning of the Digital Generation within the Philosophy of Islamic Education - Sakti Cahyo Nugroho; Luklu’ul Islamiyati; Mahmud Adaem; Rifqi Khairul Anam (Education Reserach Center, 2026)
This study analyzes the crisis of critical reasoning in modern education and formulates an ethics based critical reasoning model from the perspective of Islamic educational philosophy. Contemporary education tends to emphasize cognitive achievement and value-free rationality, producing individuals who are intellectually capable yet morally and spiritually weak. In the digital era, this condition contributes to disinformation, polarization, hate speech, and unethical debate culture. The research uses a qualitative library research method through philosophical analysis of classical and contemporary sources. Primary sources include the works of Al-Ghazali and Al-Farabi, while secondary sources consist of scholarly journals and modern literature on Islamic education, critical reasoning, and character education. Data analysis involved description, interpretation, and synthesis to construct an integrative framework combining reason, morality, and spirituality. The findings show that the crisis of critical reasoning is essentially a moral and epistemological crisis caused by the separation of reason (‘aql) from the heart (qalb) and the loss of adab before knowledge in modern education. Islamic education offers a solution through integrating reason and morality. The proposed model includes sincere intention, ethical reasoning, social benefit (maṣlaḥah), integration of ‘aql and qalb, and the formation of Insan Kamil.